Using SVM (Support Vector Machine) Method To Predict Best Seller Book In Amazon - Nengah Widya Utami; Joshael Juinor Soplantila (Primakara University, 2021)
Amazon is an American multinational technology company based in Seattle, Washington, which focuses on e-commerce, cloud computing, digital streaming, and the Big Four artificial intelligence along with Google, Apple, and Facebook. Therefore this company must have many and varied sales data. One of them is book sales data. In this study, the author is interested in analyzing best-selling book sales by implementing data mining using the SVM algorithm, where the data is taken at Kaggle.com in the form of a data set.